2020
DOI: 10.1002/jsfa.10391
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of yeasts in indigenous fermented foods and beverages of Ethiopia

Abstract: BACKGROUND As one of the origin centers of domesticated plants in the world, Ethiopia is rich in diversified fermented foods and beverages, in which yeasts are usually among the essential functional microorganisms. This study aims to investigate yeast species diversity and distribution in indigenous fermented products in Ethiopia using conventional isolation and molecular identification methods. RESULT Yeast cell counts in 221 samples of various Ethiopian traditional fermented products, including fermented sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…which have evolved to survive in the desired environment and have potentially beneficial phenotypes for industry (Steensels et al, 2014a). This could be especially relevant for the baking industry, as wild-yeast fermented breads like sourdough, injera, Indian flatbreads, and Chinese steamed bread are teeming with microbial diversity (Zhang et al, 2011;Li et al, 2016;Tamang et al, 2016;Liu et al, 2018;Tadesse et al, 2019;Koricha et al, 2020). The S. cerevisiae strain diversity in these homemade grain ferments is largely unknown, and what is known is predominantly from European and North American isolates.…”
Section: Bioprospectingmentioning
confidence: 99%
“…which have evolved to survive in the desired environment and have potentially beneficial phenotypes for industry (Steensels et al, 2014a). This could be especially relevant for the baking industry, as wild-yeast fermented breads like sourdough, injera, Indian flatbreads, and Chinese steamed bread are teeming with microbial diversity (Zhang et al, 2011;Li et al, 2016;Tamang et al, 2016;Liu et al, 2018;Tadesse et al, 2019;Koricha et al, 2020). The S. cerevisiae strain diversity in these homemade grain ferments is largely unknown, and what is known is predominantly from European and North American isolates.…”
Section: Bioprospectingmentioning
confidence: 99%
“…The high prevalence of Candida and Saccharomyces in the products is consistent with studies elsewhere that reported them as the most dominant yeasts in many foods in sub-Saharan Africa [ 25 , 26 ]. Reports have shown that S. cerevisiae is the dominant yeast in the fermentation of most indigenous food products in sub-Saharan Africa [ 27 , 28 ]. The isolation of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The str from China exhibited a moderately higher sequence diversity (π = 6.30 × 10 −3 ) than strains from rest of the world collectively (π = 5.95 × 10 −3 ). The sequence diversity o In previous population genomic studies of S. cerevisiae, African strains were poorly represented in terms of ecological and geographic origins, though Africa has a long history of fermented food production and diversified fermented foods [73,74]. Indeed, an African origin hypothesis for domesticated yeast has also been proposed [62].…”
Section: Genetic Diversity and Population Structure Of S Cerevisiaementioning
confidence: 99%
“…In previous population genomic studies of S. cerevisiae , African strains were poorly represented in terms of ecological and geographic origins, though Africa has a long history of fermented food production and diversified fermented foods [ 73 , 74 ]. Indeed, an African origin hypothesis for domesticated yeast has also been proposed [ 62 ].…”
Section: Genetic Diversity and Population Structure Of S Ce...mentioning
confidence: 99%